Charge driven metal-insulator transitions in LaMnO3|SrTiO3 (111) superlattices. (1st August 2017) - Cossu, F.; Tahini, H. A.; Singh, N.; Schwingenschlögl, U.
Abstract: Interfaces of perovskite oxides, due to the strong interplay between the lattice, charge and spin degrees of freedom, can host various phase transitions, which is particularly interesting if these transitions can be tuned by external fields. Recently, ferromagnetism was found together with a seemingly insulating state in superlattices of manganites and titanates. We therefore study the (111) oriented superlattices by means of ab initio calculations, predicting a ferromagnetic ground state due to double exchange in all cases. We shed light on the ferromagnetic coupling in the LaMnO3 region and at the interfaces. The insulating states of specific superlattices can be understood on the basis of Jahn-Teller modes and electron/hole doping.